The Practice of Underage Marriage in Bathin VIII District Positive Legal Perspectives and Islamic Law - M. Mizan Azrorizain; Hermanto Harun; Husin Bafadhal (Dinasti Publisher, 2022)
This study aims to reveal the problem of underage marriage and how according to positive law and Islamic law on this matter, with sub-focuses including: (1) Explanation of the practice of underage marriage in Bathin VIII District, Sarolangun Regency. (2) An explanation of the causes of the practice of underage marriage in Bathin VIII District, Sarolangun Regency. (3) An explanation of the perspective of positive law and Islamic law on underage marriage in Bathin VIII District, Sarolangun Regency. This study uses a descriptive qualitative research method with a variety of casuistic research. Data was collected by using in-depth interviews, observation, and documentation techniques. The data analysis technique uses interactive analysis with a cyclical interactive model. The results showed that there were three findings. First, underage marriages that occurred in Bathin VIII District, Sarolangun Regency. is a tradition that often occurs among the majority of people, so that underage marriages often occur because they think that as long as the marriage is religiously valid and the family's parents also agree, the marriage can be carried out by ignoring several things related to marriage , including the physical and psychological children and also laws. Second, the factors for the occurrence of underage marriages are low education, economic factors, and being influenced by the surrounding environment, keeping children from things that are not wanted, people have already been proposed to so